Directions of economic growth of the chemical and petrochemical industry of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2017)
In article formation of the chemical and petrochemical industry in the world and in Kazakhstan is considered. This branch is the most perspective in the world and in Kazakhstan. Without further development of this industry development of the accompanying branches, and also high-quality effective growth of national economy is impossible. Kazakhstan can become the essential player in the petrochemical market of the world and that will significantly affect a ratio of forces in the world markets ofoil. Employment has a strategic role in this industry without its increase -development of this branch andfurther prospects of scenarios of development of the market of oil is impossible.By the end of the 1990-th years from inheritance from the USSR of the largest petrochemical complexand prevoius complex is notremain in Kazakhstan which will be working continuously also as avestige: technological, enterprise, production communications also have been destabilized. In this regarddevelopment of methodical bases of economic growth of the chemical and petrochemical industryof Kazakhstan, definition of the modern directions of economic growth of chemical and petrochemicalproductions of Kazakhstan, making use of foreign experience, represents an urgent scientific task whichsolution has the extreme strategic importance for Kazakhstan. The chemical and petrochemical complexof the country, represents one of the most difficult complexes of national economy, it is also strategicbranch because it is connected with national economic security, and also with other economic indicatorsof economic growth of economy of Kazakhstan.Novelty of a research consists in the analysis of the main economic indicators of the chemical andpetrochemical industry, the offers of more effective mechanisms of economic growth of the chemicaland petrochemical industry. The forecast of oil production which will allow to carry out planning ofproduction of oil and employment in the chemical and petrochemical industry of Kazakhstan also isdeveloped. The use of new approaches in the organization of tax, investment activity of the enterprisesof the chemical and petrochemical industry is also offered.